Medical Properties of Abutilon hirtum (Lam.) Sweet (Malvaceae): A Review (Eurasian Medical Research Periodical, 2022)
Herbal drugs have less side effects, compared with the chemical medicine. Abutilon hirtum L. (Malvaceae) is a medicinal plant used as a herbal medication for many illnesses. The perennial shrub or herb, commonly named Vadathuthi or Indian mallows, found in tropical areas. Different studies on medicinal plants has been carried out to understand their medicinal properties including their cytotoxic activities, antioxidant activities, hepatoprotective activities, anti-inflammatory activities, analgesic activities, antipyretic activities, anti-diabetic activities, acute toxicity, antimicrobial properties, antimalarial and antileishmanial properties. Moreover, A. hirtum is traditionally used in India for kidney gravel pain relief, treating diarrhea, toothaches and coughs, bladder inflammation, wound & ulcer demulcent, diuretic as well as mouth wash. Thus, to prove various studies performed on different classes of phytochemicals of total ethanolic extracts with various proportions of its leaf like flavonoids, alkaloid, tannins, saponin, cardial glycoside, terpenes, rutin, steroid, phenols, fatty acid and resins in order to detect the pharmaceutical and industrial properties of A. hirtum L. Natural compounds serve as raw materials for development of many popular drugs